2004
DOI: 10.1074/jbc.m404996200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent Self-assembly of Human Centrin 2

Abstract: Human centrin 2 (HsCen2) is a member of the EF-hand superfamily of calcium-binding proteins, often associated with the centrosomes and basal bodies. These organelles exhibit different morphological aspects, including a variety of centrin-containing fibers that connect the two centrioles or other structural elements of the pericentriolar space. The molecular basis of the Ca 2؉ -sensitive fibers and their precise role in centrosome duplication are not known. To explore the possible structural role of HsCen2, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 42 publications
11
77
0
3
Order By: Relevance
“…3 also allows comparison of the more distorted loops of EF-hand sites I and II in the N-terminal and without calcium present to sites III and IV. Site I differs from the more canonical HsCen-2 site IV (or EFhand I in calmodulin) mainly by the replacement of an aspartate important for Ca 2ϩ binding by Thr 45 . An analogous comparison suggests two substitutions reduce Ca 2ϩ affinity at site II, Glu 79 rather than an asparate and Asp 88 rather than a glutamate.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…3 also allows comparison of the more distorted loops of EF-hand sites I and II in the N-terminal and without calcium present to sites III and IV. Site I differs from the more canonical HsCen-2 site IV (or EFhand I in calmodulin) mainly by the replacement of an aspartate important for Ca 2ϩ binding by Thr 45 . An analogous comparison suggests two substitutions reduce Ca 2ϩ affinity at site II, Glu 79 rather than an asparate and Asp 88 rather than a glutamate.…”
Section: Resultsmentioning
confidence: 98%
“…Titrating HsCen-2 (26,43) and other centrins (44) to Ca 2ϩ saturation is complicated by aggregation of high order oligomers, an aggregation of reversible nature. Deletion of amino acids 1-24 has little effect on protein stability, global secondary structure, or metal binding (29) but does prevent aggregation; thus, these residues must be involved in the self-assembly (45). The formation of fibers consisting of centrin may be of physiological importance in the duplication and segregation of microtubule organizing centers (21).…”
Section: Disordered Hscen-2 N-terminalmentioning
confidence: 99%
“…Previous studies suggested that HsCen-2 is dimeric and binds only two calciums per dimer, likely to site IV in each monomer [19]. Studies of an N-terminal 25 amino acid truncation of HsCen-2 suggest that the N-terminus is involved in the calcium-dependent dimerization of the protein [21]. On the other hand, Veeraraghavan et al showed that Chlamydomonas centrin-2 binds 4 mol of calcium/mol protein [22].…”
mentioning
confidence: 99%
“…Studies by Craescu and coworkers (72) demonstrated that the N-terminal extension of CETN2 mediated self-polymerization. To facilitate working with CETN2, a construct lacking the N-terminal 21 amino acids [CETN2 (22-172)] was generated.…”
Section: Rad23b and Cetn2 Stimulate The Dna-binding Activity Of Xpc-cmentioning
confidence: 99%